Ultrathin Surface Modification by Atomic Layer Deposition on High Voltage Cathode LiNi0.5Mn1.5O4 for Lithium Ion Batteries. Issue 2 (16th December 2013) - Fang, Xin; Ge, Mingyuan; Rong, Jiepeng; Che, Yuchi; Aroonyadet, Noppadol; Wang, Xiaoli; Liu, Yihang; Zhang, Anyi; Zhou, Chongwu
Abstract Atomic layer deposition (ALD) has been used to modify the surface of the high‐voltage cathode LiNi0.5Mn1.5O4 by coating ultrathin Al2O3 layers on the electrodes. The ultrathin layer can suppress the undesirable reactions during cycling while retaining the electron and ion conductivity of the electrode. The Al2O3‐coated LiNi0.5Mn1.5O4 showed remarkable improvement over bare LiNi0.5Mn1.5O4. After 200 cycles, the Al2O3‐coated cathode showed 91 % capacity retention whereas the bare LiNi0.5Mn1.5O4 can only maintain 75 % under the same testing conditions. In addition, the Al2O3‐coated LiNi0.5Mn1.5O4 retained 63 % of its capacity 900 cycles. At an elevated temperature of 55 °C, the Al2O3‐coated LiNi0.5Mn1.5O4 still delivered 116 mAh g−1 at the 100th cycle; in comparison, the capacity for bare LiNi0.5Mn1.5O4 decreased to 98 mAh g−1. According to the results from charge/discharge and AC impedance experiments, the improvement is ascribed to the reduced overpotential and Li ion surface diffusion impedance. The promising results demonstrate the potential of developing high‐energy lithium ion batteries with a long cycle life by using a highly scalable preparation method for LiNi0.5Mn1.5O4 and the broadly applicable ALD process.